2003
DOI: 10.1076/clin.17.3.331.18092
|View full text |Cite
|
Sign up to set email alerts
|

Number Processing and Calculation – Normative Data from Healthy Adults

Abstract: Despite the high incidence of numerical deficits in neurological patients, little attention has been paid to the development of diagnostic tools. In fact, most of the published reports on acquired numerical disorders, whether single case or group studies, do not refer to standardised measures of performance providing little, if any, control data specifically collected for the examination. In this study we present data of 282 healthy controls of different age groups and educational levels in a new battery of Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 57 publications
2
71
1
Order By: Relevance
“…18 Mood status was stable and no signs of depression or pathological anxiety were detected, as evaluated using the European Organisation for Research and Treatment of Cancer Quality of Life QuestionnaireCore 30 (EORTC QLQ-C30) 9 and Hospital Anxiety and Depression Scale 26 tests, respectively. The assessment of calculation skills according to the methods indicated by Delazer et al 5 showed a normal performance. In detail, the Number Processing and Calculation battery 5 included 35 tasks assessing different counting abilities, such as number comprehension, numerical transcoding, calculation, arithmetic reasoning, and conceptual knowledge.…”
Section: Preoperative and Postoperative Assessmentmentioning
confidence: 89%
See 1 more Smart Citation
“…18 Mood status was stable and no signs of depression or pathological anxiety were detected, as evaluated using the European Organisation for Research and Treatment of Cancer Quality of Life QuestionnaireCore 30 (EORTC QLQ-C30) 9 and Hospital Anxiety and Depression Scale 26 tests, respectively. The assessment of calculation skills according to the methods indicated by Delazer et al 5 showed a normal performance. In detail, the Number Processing and Calculation battery 5 included 35 tasks assessing different counting abilities, such as number comprehension, numerical transcoding, calculation, arithmetic reasoning, and conceptual knowledge.…”
Section: Preoperative and Postoperative Assessmentmentioning
confidence: 89%
“…The assessment of calculation skills according to the methods indicated by Delazer et al 5 showed a normal performance. In detail, the Number Processing and Calculation battery 5 included 35 tasks assessing different counting abilities, such as number comprehension, numerical transcoding, calculation, arithmetic reasoning, and conceptual knowledge. The calculation abilities included tasks such as simple fact retrieval, rule-based processing, and oral and written calculation in all 4 operations (addition, subtraction, multiplication, and division).…”
Section: Preoperative and Postoperative Assessmentmentioning
confidence: 89%
“…Counting serially (automatic range) in threes, in tens, and in reverse order (back to front) requires praxis skills and prior learning 20 .The fact that all tasks were altered suggests that the inferior performance of the aphasic patients resulted not only from speech apraxia, which is commonly found in aphasic patients 21 who sometimes have difficulty controlling the programming of their buccolaryngo-pharyngeal speech movements, and this gives the impression that they struggle to produce the intended sequence of sounds. They also have difficulties with verbal counting and learned numerical concepts 16,21 .…”
Section: Discussionmentioning
confidence: 99%
“…This battery is reputed to be the most frequently used method of assessing calculation abilities in adults [14][15][16] and contains 13 different tasks ( 31 subtasks; Table 2): (1) counting; (2) dot counting; (3) transcoding; (4) arithmetic signs; (5) number comparison; (6) mental computation; (7) estimating the result of an operation; (8) number positioning on an analog scale; (9) writing down an operation; (10) written calculation; (11) perceptive estimation of quantity where subjects must estimate the weight, length, or number of objects shown in a picture; (12) contextual magnitude judgments; and (13) numerical knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…Patients gave their written informed consent. A full assessment of calculation skills was performed before surgery according to the methods of Delazer et al, 3 assessing different counting abilities, number comprehension, numerical transcoding, calculation, arithmetic reasoning, and conceptual knowl- Preservation of calculation processing in brain surgery is crucial for patients' quality of life. Over the last decade, surgical electrostimulation was used to identify and preserve the cortical areas involved in such processing.…”
mentioning
confidence: 99%